Role of Interleukin-38 in Chronic Inflammatory Diseases: A Comprehensive Review - Xu, Wang-Dong; Huang, An-Fang (Frontiers in Immunology, 2018)
Interleukin (IL)-38 is the newest member of the IL-1 family. It can bind to several receptors, regulate the generation, function of inflammatory cytokines through the downstream signaling pathways. IL-38 is expressed in several tissues, such as placenta, heart and brain. It is involved in a wide variety of diseases including chronic inflammatory diseases. In this review, we discuss the expression and biological functions of IL-38, especially the role in rheumatic autoimmune diseases. Collection of the information may improve the understanding of IL-38, and may give potential for theoretical basis for clinical trials and drug development in the future